THE INTEGRATIION OF CULTURE LITERACY IN STRENGTHENING THE PROFILE OF PANCASILA STUDENTS IN SCIENCE LEARNING FOR ELEMENTARY SCHOOLS - Minsih, Minsih; Mujahid, Imam; Mukminin, Amirul; Helzi, Helzi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Cultural literacy plays a critical role in developing students’ sense of responsibility, tolerance, and national identity. In the context of 21st-century education, it is a key component of the Pancasila Student Profile, which guides character formation in Indonesian schools. While cultural literacy is often linked with language and social studies, this research explores its integration into science learning in elementary schools. The aim is to identify how cultural values, local wisdom, and scientific inquiry are harmonized to support holistic student development through the Independent Curriculum. This qualitative study employed a phenomenological design, focusing on two Sekolah Penggerak (Driving Schools): Elementary School Muhammadiyah 1 Ketelan and Elementary School Muhammadiyah Plus Malangjiwan. Participants included school principals, teachers, and students. Data collection was conducted through observations and in-depth interviews, using structured interview sheets. Data were analyzed through data reduction, presentation, and conclusion drawing, with validity ensured through source triangulation. The results revealed that cultural literacy was embedded in science learning through the contextualization of scientific concepts with local wisdom such as using traditional tools in experiments, exploring environmental stewardship rooted in local customs, and incorporating indigenous knowledge into ecology topics. Activities like science-based cultural exhibitions, traditional games with scientific principles, and the use of regional languages in science discussions strengthened student engagement and cultural identity. This study offers a novel integration of cultural literacy into science education, demonstrating how localized, culturally responsive teaching can enrich scientific understanding while reinforcing national character in line with the Pancasila Student Profile.